An in-depth analysis of the personal factors and their pathways in shaping self-directed learning abilities among undergraduate nursing students - Li, Xiangxiang; Wang, Meifang; Feng, Xiujuan; Yin, Xiumin; Liang, Juan (Frontiers in Psychology, 2024)
Developing self-directed learning in undergraduate nursing students affects not only their learning and their lives, but also their future professional development and the quality of their future clinical nursing work. Therefore, it is important to focus on and foster self-directed learning in undergraduate nurse students. Through stratified random sampling, this study selected nursing undergraduates from a Chinese university to understand the influencing factors of their self-directed learning, and explored the relationship between metacognition and self-directed learning ability, as well as the role of psychological capital and interpersonal communication ability in the relationship. This study effectively investigated 639 undergraduate nursing students, and found that the metacognition, psychological capital and interpersonal communication affected their self-directed learning ability, and the four were correlated with each other, in which psychological capital and interpersonal communication ability played a chain mediating role between the metacognition and self-directed learning ability of undergraduate nursing students. This study suggests that undergraduate nursing students can improve their self-directed learning ability by improving their psychological capital level and interpersonal communication ability when metacognition is difficult to change.